2017
DOI: 10.1093/mmy/myx098
|View full text |Cite
|
Sign up to set email alerts
|

Experimental sporotrichosis in a cyclophosphamide-induced immunosuppressed mice model

Abstract: This report describes a model of host resistance for Sporothrix schenckii, an opportunistic fungi in immunosuppressed mice with cyclophosphamide (CY) to be used in studies of immunotoxicology and immunopharmacology. Two doses of CY were administered intraperitoneally: 200 mg/kg and a booster of 150 mg/kg at 9-day intervals. Three days after the first dose of CY the animals were infected subcutaneously with 1.8 × 108 yeast/ml (S. schenckii ATCC 16345). At 7 and 14 days post-infection, the animals were euthanize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…infection in these animals. In fact, experimental models have shown that the efficiency of the immune response will affect the control of fungal burden [ 23 , 24 , 25 , 26 ]. Similarly, in humans and dogs, the occurrence of lesions with high fungal burdens is usually associated with immunosuppressive conditions, such as malnutrition, use of steroid, and the presence of underlying diseases, especially those that induce immunosuppression, such as AIDS [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…infection in these animals. In fact, experimental models have shown that the efficiency of the immune response will affect the control of fungal burden [ 23 , 24 , 25 , 26 ]. Similarly, in humans and dogs, the occurrence of lesions with high fungal burdens is usually associated with immunosuppressive conditions, such as malnutrition, use of steroid, and the presence of underlying diseases, especially those that induce immunosuppression, such as AIDS [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, chemotherapeutics drugs often generate many harmful side effects such as cytotoxic effects and host immunosuppression, no matter how great of their therapeutic effects are [ 4 ]. Cyclophosphamide (Cy), an alkylating agent, has been widely used as chemotherapeutic drug which results in a lot of adverse effects including immunosuppression, bone marrow suppression, leucopenia and oxidative stress [ 5 , 6 , 7 , 8 ]. It has been reported that Cy can generate oxidative stresses, mediate disruption of the redox balance, and lead to biochemical and physiological disturbances [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…After inoculation, several mechanisms of the innate immunity are activated to control the infection directly and by stimulating the specific immune response (Carlos et al, 1994;Gonçalves et al, 2015;Ferreira et al, 2015;Maia et al, 2016;Jellmayer et al, 2017). The importance of these immune mechanisms for the control of S. schenckii-infection is evidenced by the higher fungal colonization and dissemination in immunosuppressed mouse models (Manente et al, 2018;Batista-Duharte et al, 2018a) and immunocompromised patients, mainly individuals with HIV-AIDS (Moreira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%